The Insects Visitor on Wild Israeli Grass Flowers (Asystasia gangetica (L.) T. Anderson) - Sumah, Astrid Sri Wahyuni (Indonesian Journal of Applied Research (IJAR), 2024)
Insects are invertebrate fauna that are important in various ecosystems and have high diversity and adaptability to various habitats. Insect diversity plays an important role (pollinator, pest control, or natural enemy) in several sectors, such as agriculture, ecology, human health, and natural resources. Apart from their beneficial role, the presence of insects can also be detrimental to humans; for example, insects can cause damage to agricultural products. Therefore, this research aimed to determine the diversity and role of insect visitors to the flowers of the Israeli grass plant (Asystasia gangetica). The research was carried out using a scan sampling survey method around community settlements, especially locations that various wild plants still cover. The research results showed that ten species and 255 individual insects visited Israeli grass flowers, which were divided into five orders, namely Lepidoptera, Coleoptera, Hemiptera, Diptera, and Hymenoptera. The order Lepidoptera is a flower-visiting insect species with the highest abundance and is a pollinator. Flowering plants that grow wild, such as Israel grass, benefit society indirectly by being used as traditional medicine. However, they also positively impact the diversity of flower-visiting insects. The presence of flower-visiting insects that work around grass indirectly has the potential to conserve beneficial grass plants but is underestimated by the community.